Role of Pregabalin in Treatment of Polyneuropathy in Multiple Myeloma Patients: A Retrospective Study. Issue 5 (September 2019) - Maschio, Marta; Mengarelli, Andrea; Zarabla, Alessia; Giannarelli, Diana; Maialetti, Andrea; Gumenyuk, Svetlana; Renzi, Daniela; Palombi, Francesca; Pisani, Francesco; Romano, Atelda; Spadea, Antonio; Galiè, Edvina; et al.
Abstract : Objectives: Polyneuropathy (PN) is a frequent and significant clinical manifestation of multiple myeloma that may be observed at onset of disease or induced during treatment as a therapy-related complication. Polyneuropathy may be a relevant issue in myeloma patients owing to its significant impact on the quality of life, considering that it may lead to dose reduction or treatment discontinuation. The present retrospective study intended to evaluate efficacy of pregabalin (PGB) in treatment of PN in multiple myeloma patients. Materials and Methods: Medical charts of 108 consecutive PN myeloma patients were reviewed. Data regarding the tumor history and therapy as well as the clinical and neurophysiological examinations 6 months before and after initiation of PGB therapy were collected. Results: Thirty-eight medical charts had all the requested information. All patients (n = 38) underwent bortezomib-based treatment; 19 were previously treated and 19 were treatment naive. At first neurologic visit, all patients had PN symptoms (grade 2 of National Cancer Institute—Common Toxicity Criteria) without relevant pain. Neurophysiological evaluation showed a significant decrease in sensory nerve action potential amplitude ( P = 0.006), conduction velocity ( P = 0.006), and distal latency ( P = 0.03) of sensory nerves between the first and the last neurological examination, in all patient population. Similar results were observed in treatment-naive patients, when the study cohort was stratified according to previous treatment. On the contrary, no significant differences were found between the first and the last neurophysiological follow-up evaluation in previously treated patients. Six months after PGB treatment, all patients reported disappearance of neurological symptoms (grade 0 National Cancer Institute—Common Toxicity Criteria). Conclusions: In this retrospective study, improvement in neurological symptoms during PGB therapy was observed in the total population, despite the presence of a distal, sensory axonal neuropathy, as evidenced by neurophysiological examination.